Predicting water distribution pipe failures using machine learning and cross-infrastructure data - Kozelj, Daniel (Acta hydrotechnica, 2025)
Water pipeline failures in urban networks are a significant source of non-revenue water, service disruptions, and high maintenance costs. This study develops a machine learning model to predict pipeline failure probabilities and inform risk-based maintenance strategies. Trained on real-world assets and geospatial data from 2010 to 2025, the model incorporates standard pipe attributes – such as material, age, diameter, network type, and maintenance history – alongside spatially derived indicators of the surrounding infrastructure. Notably, it quantifies the predictive impact of adjacent infrastructure systems, including electricity grids, gas pipelines, district heating, sewage systems, and roads, utilizing spatial buffering and overlay techniques. Several of these cross-utility features, particularly road category, electricity voltage, and sewer type, showed meaningful predictive importance, reflecting their indirect but consistent influence on the risk of pipe failure. The ML model, built with the XGBoost algorithm and validated through stratified K-fold cross-validation, achieved high performance (ROC AUC: 0.9102, recall: 0.7750, accuracy: 0.8750). Despite lower precision due to class imbalance, the F1 score (0.2261) and LogLoss (0.2500) confirm its reliability. This study introduces a novel, spatially enriched approach to failure prediction, advancing urban infrastructure management through context-aware, data-driven insights.
Keywords: condition assessment; machine learning; napovedovanje okvar cevovodov; ocenjevanje stanja; pipe failure prediction; prostorska analiza; spatial analysis; strojno učenje; vodovodni sistemi; water distribution systems; XGBoost